Sexual Violence, the Principle of Legality, and the Trial of Hissène Habré - Kim Thuy Seelinger; Naomi Fenwick; Khaled Alrabe (Washington University Journal of Law & Policy, 2020)
The appeals panel of the Extraordinary African Chambers in the Courts of Senegal upheld the former president of Chad’s, Hissène Habré’s, conviction for war crimes, crimes against humanity, and acts of torture. This ruling stands out as the trial court’s convictions included rape and sexual slavery as crimes against humanity, which observers hailed as a tremendous victory for international criminal justice and rights of sexual violence survivors. Specifically, in Habré’s case, the determination turned on whether the crimes were considered violations of international law at the times they were committed. Using historical examples from various tribunals, the brief argued that the acts of sexual violence before the EAC were crimes under international law in the 1980s. Though not submitted on the official court record, this brief provided guidance to the tribunal, which ultimately upheld Habré’s conviction.
Keywords: Hissène Habré; international criminal justice; international law; sex; sexual violence; sexual slavery; rape